Analisa Yuridis Faktor Yang Menjadi Penghambat Bagi Masyarakat Dalam Membayar Pajak Bumi dan Bangunan Daerah Kabupaten Purwakarta - Resta Septia Arman; Margo Hadi Pura (Jurnal Ilmiah Wahana Pendidikan, 2023)
Land and Building Tax is one of the main sources of income for a region. Land and building tax revenues can later be used as a source to increase the progress and welfare of society, including to improve the welfare of the poor so that their lives can improve. From this utilization it can be judged that the receipt of Land and Building Tax revenue has elements of equity and justice. The purpose of this research is to find out what factors are the obstacles for people in paying land and building tax. The type of research used is qualitative research. Source of data obtained from primary and secondary data. Primary data through direct observation and interviews with BAPENDA staff in Purwakarta Regency. The results of this study are that the factors that inhibit public awareness in paying Land and Building Tax (PBB) are people's indifference, administrative data discrepancies, uncertain economics and the lack of conditions for the construction of facilities and infrastructure in the Purwakarta district, thereby increasing a sense of egoism. has been ingrained in society to not pay taxes is increasing.